Problem-Based Learning in Algebra: Fostering Critical Thinking Skills Among Middle School Students - Ovan Ovan; Sitti Fatimah Sangkala Sirate; Mulyati Mulyati (Institute of Multidisciplinary Research and Community Service, 2026)
This study examines the effectiveness of Problem-Based Learning (PBL) in improving Grade 8 students’ critical thinking skills in algebraic problem solving. A quasi-experimental design was employed with 53 students, divided equally between an experimental group receiving PBL instruction and a control group receiving conventional instruction. Students’ critical thinking abilities were measured with pre- and post-tests, and the data were analyzed with independent-samples t-tests, paired-samples t-tests, normalized gain (N-gain), and effect size. The results revealed that both groups had comparable initial abilities, as indicated by the non-significant difference in pre-test scores. However, after the intervention, the experimental group achieved a significantly higher mean score compared to the control group (p 0.001). Within-group analysis showed that both groups improved significantly, but the magnitude of improvement was substantially greater in the PBL group. This is further supported by the N-gain results, which showed that the experimental group reached the moderate-to-high category, while the control group remained in the moderate category. The calculated effect size (d = 1.26) indicates a strong practical impact of PBL on students’ critical thinking skills. Additionally, gender-based analysis showed no significant differences, suggesting that PBL is equally effective for both male and female students. These findings indicate that Problem-Based Learning (PBL) creates a more effective environment for enhancing students’ critical thinking skills through structured problem-solving activities, collaborative discussions, and reflective reasoning processes. The study emphasizes the significance of student-centered learning approaches in mathematics education and recommends integrating PBL into classroom instruction to promote higher-order thinking skills and deeper conceptual understanding among students. Keywords: Problem-Based Learning, Critical Thinking Skills, Algebra, Middle School Students.